Utility Evaluation of Porcine Enteroids as PDCoV Infection Model in vitro - Luo, Hao; Zheng, Jingyou; Chen, Yunlu; Wang, Tingjun; Zhang, Zhenning; Shan, Ying; Xu, Jidong; Yue, Min; Fang, Weihuan; Li, Xiaoliang (Frontiers in Microbiology, 2020)
Intestinal enteroids, which partially recreate the structure and function of the intestinal villi-crypt, have many physiological similarities of the intestinal tissues in vivo. Enteroids have been shown to have certain advantages in the host and intestinal pathogens’ interaction model. In this study, intestinal crypts from porcine duodenum, jejunum and ileum were isolated, cultured and transformed into porcine intestinal enteroids in vitro. Enterocytes, enteroendocrine cells, Paneth cells, stem cells, TA proliferating cell and goblet cells were observed in the differentiated enteroids. The porcine deltacoronavirus (PDCoV) could be detected in the infected cultured enteroids by immunofluorescence assay (IFA) and real-time RT-PCR analysis. Double immunofluorescence labelling assay demonstrated that that the PDCoV existed in intestinal enterocytes and stem cells. Multiple cellular responses, mainly including the fluctuation in the transcription of genes related to mucosal immunity, antiviral genes, stem cells and other cell marker genes, could be monitored in the enteroids infected by PDCoV. Our experiments show that PDCoV can proliferate in cultured enteroids in vitro leading to diverse cellular responses. This study provided a novel infection model for PDCoV in vitro to gain further insights on the interaction mechanism between host and porcine intestinal pathogens.